The perceptions of management on the benefits of adopting an environmental management accounting system as a waste management tool - Mishelle Doorasamy (Foundations of Management, 2016)
The purpose of this paper is to ascertain the perception of management on the benefits of adopting an environmental management accounting (EMA) system as a waste management tool in a paper and pulp manufacturing company. This paper highlights the benefits of an EMA system and the role and importance of EMA as a decision-making tool in encouraging the adoption of cleaner production (CP) techniques and technologies. This research was based on a case study of a paper and pulp manufacturing company in KwaZulu-Natal. This research was both quantitative and qualitative in nature. Data collection instruments for the study included a Likert-type questionnaire and interviews with the environmental manager and cost accountant but the findings reported in this paper are based on the empirical evidence gathered from the questionnaire which identified that there was positive correlation between environmental performance and CP techniques and technologies. Environmental costs were hidden under general overheads and understated because the company was using a conventional costing system and not an EMA system; hence, environmental costs were not traced back to the products or processes responsible for those costs. It was evident from the qualitative data analysis that management regarded their environmental costs as too insignificant to justify implementation of an EMA system. The consequent reluctance of the company to adopt CP resulted in poor waste management and lower-quality environmental performance.
Keywords: 650; environmental performance; environmental management accounting systems; cleaner production; waste management